1985
DOI: 10.1095/biolreprod32.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Density Lipoprotein on Estradiol Stimulation of Luteal Steroidogenesis 1

Abstract: The aim of this investigation was to determine whether luteal cells utilize cholesterol derived from high-density lipoprotein (HDL) for steroidogenesis and whether estrogen enhances luteal utilization of exogenous sterol. Incubation of Day 15 corpora lutea (CL) with different doses of human HDL resulted in a dose-dependent increase in progesterone production. HDL in vitro enhanced the overall steroidogenic capacity. However, the percentage of increases in 17 alpha-hydroxyprogesterone, testosterone and estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Thus, the increase in ERβ may have increased the ovarian response to circulating E 2 , which in turn stimulates cyp19A1 aromatase expression and E 2 synthesis. These data suggest that the negative feedback exerted by E 2 may be partially blocked in HypoT rats, sensitizing the ovary to E 2 actions during P and E. Since it has been largely demonstrated that, in the rat, E 2 stimulates steroidogenesis and luteal hypertrophy and synergizes with the effect of PRL in the ovary, these factors may promote corpus luteum survival favouring the establishment of pseudopregnancy [26,34-37]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increase in ERβ may have increased the ovarian response to circulating E 2 , which in turn stimulates cyp19A1 aromatase expression and E 2 synthesis. These data suggest that the negative feedback exerted by E 2 may be partially blocked in HypoT rats, sensitizing the ovary to E 2 actions during P and E. Since it has been largely demonstrated that, in the rat, E 2 stimulates steroidogenesis and luteal hypertrophy and synergizes with the effect of PRL in the ovary, these factors may promote corpus luteum survival favouring the establishment of pseudopregnancy [26,34-37]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the rat ovary appears to utilize high density lipoproteins (HDL) as a preferred cholesterol source for steroid production [66], the diabetes-associated increase in very low density lipoprotein that coincides with the marked decline in hepatic HDL levels [20] may limit ovarian (CL) steroid production. Although the CL can synthesize cholesterol de novo [67], the magnitude of the lipoprotein imbalance in diabetes with the significant decrease in HDL-derived cholesterol may exceed the synthetic capacity of the ovary to generate endogenous cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…We originally thought that the involvement of HSD17B7 in cholesterol biosynthesis in the corpus luteum is of little importance because the cholesterol used by the ovary originates from circulating lipoprotein (34,35). However, the marked expression of this enzyme in the fetal brain and the fact the viability of neurons depends on the intracellular cholesterol content and not on the intermediate nonsterol isoprenoid products (30) made us reconsider the importance of this activity in brain formation.…”
Section: Fig 6 Expression Of Hsd17b7 In the Embryo By In Situ Hybrimentioning
confidence: 99%